PRODUKTIVITAS DAN BIAYA ANGKUTAN KAYU DENGAN REL BAJA DAN REL KAYU - Dulsalam Dulsalam (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
The paper presents the result of a study on the productivity and cost of haulage on steel and wooden rails. The study was conducted at 4 logging companies in West Kalimantan during year 1982. There were 2 methods of log haulage observed, namely using locomotive and manual pushing.The logging companies generally used rail weighing 7 - 10 kg/m and 5 x 7 cm wooden rail. The distance between steel and wooden rails were respectively 60 - 70 cm and 60 cm or less. The crew size varied from 8 to 12 men for locomotive haulage consisting of 12 - 16 lorries, and 2 - 4 men/lorry for haulage on wooden rail. The result of the haulage study reveals also the productivity figures of respectively 156.9 m3 km/hour and 2.4 m3 km/hour for the first and the second methods mentioned above. Log transportation on steel rail is safer for the labour compared with that on wooden rail, and the life of steel rail is much longer than that, of wooden rail. Although steel rail is higher in the investment cost compared with woode'n rail (Rp 14 - 21 million/km and Rp 2.35 million/km respectively), the average haulage cost per m3' km is about one-third of the latter (Rp 80.1/m3 km and Rp 254.4/m3 km respectively).